Bayesian biomarker-driven outcome-adaptive randomization with an imperfect biomarker assay. (April 2021) - Garcia Barrado, Leandro; Burzykowski, Tomasz
Objective: We investigate the impact of biomarker assay's accuracy on the operating characteristics of a Bayesian biomarker-driven outcome-adaptive randomization design. Methods: In a simulation study, we assume a trial with two treatments, two biomarker-based strata, and a binary clinical outcome (response). P bt denotes the probability of response for treatment t ( t = 0 or 1) in biomarker stratum ( b = 0 or 1). Four different scenarios in terms of true underlying response probabilities are considered: a null ( P 00 = P 01 = 0.25, P 10 = P 11 = 0.25) and consistent ( P 00 = P 10 = 0.25, P 01 = 0.5) treatment effect scenario, as well as a quantitative ( P 00 = P 01 = P 10 = 0.25, P 11 = 0.5) and a qualitative ( P 00 = P 11 = 0.5, P 01 = P 10 = 0.25) stratum-treatment interaction. For each scenario, we compare the case of a perfect with the case of an imperfect biomarker assay with sensitivity and specificity of 0.8 and 0.7, respectively. In addition, biomarker-positive prevalence values P ( B = 1) = 0.2 and 0.5 are investigated. Results: Results show that the use of an imperfect assay affects the operational characteristics of the Bayesian biomarker-based outcome-adaptive randomization design. In particular, the misclassification causes a substantial reduction in power accompanied by a considerable increase in the type-I error probability. The magnitude of these effects depends on the sensitivity and specificity of the assay, as well as on the distribution of the biomarker in the patient population. Conclusion: With an imperfect biomarker assay, the decision to apply a biomarker-based outcome-adaptive randomization design may require careful reflection.